Effect of Financial Distress and Company Size on Audit Delay (Study on Property & Real Estate Companies Listed on the IDX in 2017 – 2019) - palupi, yoppy (International Journal of Economics, Business, and Entrepreneurship, 2021)
This study aims to determine the effect of financial distress and company size on audit delay studies on property and real estate companies listed on the Indonesia Stock Exchange in 2017 – 2019. The population in this study are all property and real estate sub-sector companies listed on the Indonesia Stock Exchange in 2017. 2017-2019 the method used is the purposive sampling method, namely the determination of samples from the existing population based on criteria. The analysis technique used in this research is multiple linear regression. Based on the results of the analysis, it was found that the financial distress variable partially had a significant negative effect on audit delay, company size partially affected audit delay. Financial Distress and Company Size simultaneously have a significant effect on Audit Delay. The limitation of this research is that the scope of the research is limited to property and real estate companies. This research is useful to provide information and as material for consideration regarding investment decisions that will be made by investors and potential investors, besides that it also provides input to companies listed on the Indonesian stock exchange as consideration in making decisions by company management. .